2019
DOI: 10.1108/jfmm-02-2018-0021
|View full text |Cite
|
Sign up to set email alerts
|

CSR-consumption paradox: examination of UK apparel companies

Abstract: This document is the author's post-print version, incorporating any revisions agreed during the peer-review process. Some differences between the published version and this version may remain and you are advised to consult the published version if you wish to cite from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 63 publications
(95 reference statements)
0
3
0
1
Order By: Relevance
“…In fashion industry, sustainability is a mandatory topic for researchers and practices [ [130] , [131] , [132] ]. Sustainable fashion consumption behavior is defined as a variety of behaviors that consumers are willing to minimize regarding their fashion consumption decisions [ 130 ].…”
Section: Results Of Topic Modeling and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fashion industry, sustainability is a mandatory topic for researchers and practices [ [130] , [131] , [132] ]. Sustainable fashion consumption behavior is defined as a variety of behaviors that consumers are willing to minimize regarding their fashion consumption decisions [ 130 ].…”
Section: Results Of Topic Modeling and Discussionmentioning
confidence: 99%
“…Sustainable fashion consumption behavior is defined as a variety of behaviors that consumers are willing to minimize regarding their fashion consumption decisions [ 130 ]. It has been alarming especially in fast fashion industry because of the life cycle of fast fashion products, including products acquisition and disposal, are short with no sustainable plans to reduce any negative impacts [ 132 ]. Harris et al [ 133 ] argued that consumers should be exposed to more sustainable and higher quality fashion products to achieve sustainable fashion consumption, in which fast fashion business pursues more trendy styles with affordable prices and low–quality materials that end up to short life–cycle of products [ 134 ].…”
Section: Results Of Topic Modeling and Discussionmentioning
confidence: 99%
“…Some recent calls in the existing literature acknowledge that CSR may be helpful in generating positive emotions among customers, such as a feeling of BA (Bagozzi et al, 2020; Castro‐González et al, 2019). The bulk of the literature has already identified that customers' purchase decision is strongly influenced by how a brand stands on social issues (Pradhan, 2018; Yu et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…El consumo de los hogares genera cerca del 72% de las emisiones de gases de efecto invernadero (Hertwich & Peters, 2009), la producción de residuos domésticos y aguas residuales (Toledo & Morocho, 2016). De ahí que constantemente se busque en la sociedad implementar acciones de consumo con menor impacto (Yu et al, 2019) dado que el consumidor es considerado un factor central en la sostenibilidad (Van et al, 2021).…”
Section: Introductionunclassified